The spectroscopic orbits and physical parameters of GG Carinae - Marchiano, Paula Esther (2012)
Aims. GG Car is an eclipsing binary classified as a B[e] supergiant star. The aims of our study are to improve the orbital elements of the binary system in order to obtain the actual orbital period of this system. We also compare the spectral energy distribution of the observed fluxes over a wide wavelength range with a model of a circumstellar envelope composed of gas and dust. This fitting allows us to derive the physical parameters of the system and its environment, as well as to obtain an estimation of the distance to GG Car. Methods. We analyzed about 55 optical and near infrared spectrograms taken during 1996-2010. The spectroscopic orbits were obtained by measuring the radial velocities of the blueshifted absorptions of the He I P-Cygni profiles, which are very representative of the orbital motion of both stars. On the other hand, we modeled the spectral energy distribution of GG Car, proposing a simple model of a spherical envelope consisting of a layer close to the central star composed of ionized gas and other outermost layers composed of dust. Its effect on the spectral energy distribution considering a central B-type star is presented. Comparing the model with the observed continuum energy distribution of GG Car, we can derive fundamental parameters of the system, as well as global physical properties of the gas and dust envelope. It is also possible to estimate the distance taking the spectral regions into account where the theoretical data fit the observational data very well and using the set of parameters obtained and the value of the observed flux for different wavelengths. Results. For the first time, we have determined the orbits for both components of the binary through a detailed study of the He I lines, at λλ4471, 5875, 6678, and 7065 Å, thereby obtaining an orbital period of 31.033 days. An eccentric orbit with e = 0.28 and a mass ratio q = 2.2 ± 0.9 were calculated. Comparing the model with the observed continuum energy distribution of GG Car, we obtain T eff = 23 000 K and log g = 3. The central star is surrounded by a spherical envelope consisting of a layer of 3.5 stellar radii composed of ionized gas and other outermost dust layers with E B-V = 0.39. These calculations are not strongly modified if we consider two similar B-type stars instead of a central star, provided our model suggests that the second star might contribute less than 10% of the primary flux. The calculated effective temperature is consistent with an spectral type B0-B2 and a distance to the object of 5 ± 1 kpc was determined.